Estimating and Removing the Sampling Biases of the AIRS Obs4MIPs V2 Data. Issue 12 (3rd December 2020) - Tian, Baijun; Hearty, Thomas
Abstract: The Atmospheric Infrared Sounder (AIRS) Observations for Model Intercomparison Projects (Obs4MIPs) Version 2.0 (V2.0) monthly mean tropospheric air temperature, specific humidity, and relative humidity profile data were designed for climate model evaluation in the context of the Coupled Model Intercomparison Project (CMIP). Due to the limitations of the Aqua satellite orbit and the AIRS retrieval algorithm, the sampling biases of the AIRS Obs4MIPs V2.0 data can be large for certain cases and must be considered when the AIRS Obs4MIPs V2.0 data are used for climate model evaluation. In this study, we estimate the sampling biases of the AIRS Obs4MIPs V2.0 data based on the fifth generation of the European Centre for Medium‐Range Weather Forecasts (ECMWF) (ERA5) reanalysis and cross‐check them using the Modern‐Era Retrospective Analysis for Research and Application, Version 2 (MERRA‐2) reanalysis. We then remove the estimated sampling biases from the AIRS Obs4MIPs V2.0 data and produce the sampling‐bias‐corrected AIRS Obs4MIPs V2.1 data that have been published at the Earth System Grid Federation (ESGF) data centers and should be used in the future for climate model evaluation. Plain Language Summary: We have estimated and cross‐checked the sampling biases of the Atmospheric Infrared Sounder (AIRS) Observations for Model Intercomparison Projects (Obs4MIPs) V2.0 data and produced the sampling‐bias‐corrected AIRS Obs4MIPs V2.1 data that should be used in the future for climate model evaluation. Key Points: The sampling biases of the AIRS Obs4MIPs V2.0 data are estimated based on ERA5 reanalysis and cross‐checked based on MERRA‐2 reanalysis The sampling‐bias‐corrected AIRS Obs4MIPs V2.1 data are produced by removing the sampling bias estimates based on ERA5 The new AIRS Obs4MIPs V2.1 data have been published on ESGF and should be used in the future for climate model evaluation